2016
DOI: 10.1038/srep36856
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres are elongated in older individuals in a hibernating rodent, the edible dormouse (Glis glis)

Abstract: Telomere shortening is thought to be an important biomarker for life history traits such as lifespan and aging, and can be indicative of genome integrity, survival probability and the risk of cancer development. In humans and other animals, telomeres almost always shorten with age, with more rapid telomere attrition in short-lived species. Here, we show that in the edible dormouse (Glis glis) telomere length significantly increases from an age of 6 to an age of 9 years. While this finding could be due to highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 65 publications
(77 reference statements)
7
78
2
Order By: Relevance
“…Telomere elongation, particularly in qPCR‐based studies, is often attributed to measurement error (Steenstrup et al, ; Verhulst et al, ). It is, however, becoming more apparent in wild population studies that telomeres do elongate (Fairlie et al, ; Hoelzl, Cornils, Smith, Moodley, & Ruf, ; Hoelzl, Smith, et al, ; Kotrschal, Ilmonen, & Penn, ; Spurgin et al, ). Our study supports this, using monochrome multiplex qPCR that, in principle, reduces measurement error due to reactions occurring in the same well.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere elongation, particularly in qPCR‐based studies, is often attributed to measurement error (Steenstrup et al, ; Verhulst et al, ). It is, however, becoming more apparent in wild population studies that telomeres do elongate (Fairlie et al, ; Hoelzl, Cornils, Smith, Moodley, & Ruf, ; Hoelzl, Smith, et al, ; Kotrschal, Ilmonen, & Penn, ; Spurgin et al, ). Our study supports this, using monochrome multiplex qPCR that, in principle, reduces measurement error due to reactions occurring in the same well.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies found no differences in telomere length between males and females in mammals (Gardner, Kimura, & Chai, ; Hoelzl et al., ), most studies showed that females typically exhibit longer telomeres than males, presumably because of lower telomere loss due to stimulating effects of oestrogen on telomerase (Smith, Mattison, & Desmond, ; Müezzinler, Zaineddin, & Brenner, ; Watson et al., ). In sharp contrast, we found longer telomeres in male mandrills than in females.…”
Section: Discussionmentioning
confidence: 99%
“…One well‐known reported benefit of hibernation is avoidance of predation, which has been illustrated in several hibernating species, where hibernating individuals show higher survival rates compared to nonhibernating counterparts . Moreover, a correlation between hibernation and longevity has been proposed for a number of hibernators, including Cheirogaleus medius . More comprehensive ecophysiological studies across dwarf lemur species and habitats are needed to determine whether there is strong phylogenetic signal in the use of hibernation.…”
Section: Phenology Of Dwarf Lemur Hibernation: To Hibernate or To Hibmentioning
confidence: 99%
“…[71][72][73] Moreover, a correlation between hibernation and longevity has been proposed for a number of hibernators, including Cheirogaleus medius. 68,74 More comprehensive ecophysiological studies across dwarf lemur species and habitats are needed to determine whether there is strong phylogenetic signal in the use of hibernation. Studies in captivity, additionally, could aid in understanding the genetic and molecular mechanisms involved in hibernation, for example, metabolic switches between sugar to lipid metabolism, under controlled conditions.…”
Section: Figurementioning
confidence: 99%